MENGINTEGRASIKAN PEMBELAJARAN AL-QUR’AN HADITS DALAM MATERI MENULIS DI MADRASAH IBTIDAIYAH MIN 1 DELI SERDANG - azhari, putri; Muhammad Alfiansyah; Adi Zulkifli BoangManalu; Gadis Ayuni Putri (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2023)
This study describes the learning of Al-Qur'an Hadith in madrasah ibtidaiyah which focuses on students' experiences and perceptions in students' writing materials. The type of research in this paper is descriptive qualitative. Qualitative Research encourages understanding of the substance of an event. Thus, qualitative research is not only to fulfill the researcher's desire to get an overview/explanation, but also helps to get a deeper explanation. Data collection techniques are used by means of interviews and also various sources, both from relevant books and journals. The results of this study indicate that the learning of Al-Qur'an Hadith at MIN 1 Deli Serdang school is: (1) There are some students who do not understand learning to read and write the Al-Qur'an. (2) The method used in the Min 1 Deliserdang school was not fully implemented due to insufficient time allocation. (3) Students at the MIN 1 Deli Serdang school write verses of the Koran that are not in accordance with the rules. (4) There are facilities in the form of inadequate facilities and infrastructure, especially when the learning process takes place, such as learning media or learning tools at MIN 1 Deli Serdang school so that educators feel the learning process is not running effectively and efficiently. Keywords: Learning, Al-Qur'an Hadits and Writing